IMPACT OF STEAM TREATMENT ON THE PHYSICAL AND MECHANICAL PROPERTIES OF HYBRID PARTICLEBOARD SENGON WOOD AND BETUNG BAMBOO - Muhamad, Soleh; Widiyanto, Wahyu; Ramadhan, Zaky Oktavian; Mangurai, Silvia Uthari NM (Universitas Tanjungpura, 2025)
This objective of this research was to assess the mechanical and physical properties of hybrid particleboard made from sengon wood (Falcataria moluccana) and betung bamboo (Dendrocalamus asper) treated with steam and used different ways of combining particleboard layer. Steam treatment was performed in the autoclave at 126 ºC for 60 minutes at a pressure of 0.14 MPa. The particleboard combinations were made based on face : core : back with three types of combinations, namely sengon particleboard, sengon : betung : sengon particleboard, and betung : sengon : betung particleboard. The boards were made of 30x30x0.9 cm³ dimensions using urea formaldehyde (UF) adhesive to achieve density of 0.6 g/cm³. JIS A 5908-2003 were used as references for the physical and mechanical properties examination. The resulting density and MC values were 0.61-0.63 g/cm³ and 10.18-10.85%, while the WA and TS values were 50.79%-74.07% and 8.81-21.84%. The MOE and MOR values produced were 331-1642 MPa and 4-12 MPa. From this study we can conclude that the hybrid particleboard made from a combination of betung : sengon : betung treated with steam was the most superior and proved to improve the mechcanical and physical properties of hybrid particleboard from sengon wood and betung bamboo. Keywords: betung bamboo, hybrid, particle board, sengon wood, steam. Abstrak Tujuan studi ini yaitu mengevaluasi sifat fisis dan mekanis papan partikel hibrida kayu sengon (Falcataria moluccana) dan bambu betung (Dendrocalamus asper) melalui pengolahan steam dan variasi kombinasi lapisan papan partikel. Pengolahan steam diterapkan dengan autoklaf pada suhu 126 ºC selama 60 menit dengan tekanan 0,14 MPa. Kombinasi papan partikel dibuat berdasarkan face : core : back dengan 3 jenis variasi kombinasi yaitu papan partikel sengon, papan partikel sengon : betung : sengon dan papan partikel betung : sengon : betung. Perekat urea formaldehida (UF) digunakan untuk membuat papan dengan ukuran 30x30x0,9 cm3 dan kerapatan target 0,6 g/cm3. Pengujian sifat fisis dan mekanis papan partikel hibrida diterapkan berdasarkan ketentuan JIS A 5908-2003. Kerapatan dan KA yang dihasilkan yaitu 0,61-0,63 g/cm3 dan 10,18-10,85%, Nilai DSA dan PT yang dihasilkan yaitu 50,79%-74,07% dan 8,81-21,84%, Nilai MOE dan MOR yang dihasilkan yaitu 331-1642 MPa dan 4-12 MPa. Hasil penelitian menunjukkan bahwa papan partikel hibrida kombinasi betung : sengon : betung dengan perlakuan steam merupakan papan partikel yang paling unggul dan terbukti dapat memperbaiki sifat fisis dan mekanis papan partikel hibrida kayu sengon dan bambu betung. Kata kunci: bambu betung, hibrida, kayu sengon, papan partikel, steam